THU0039 Lipidomics analysis of hdl particle in inflammatory rheumatic diseases: alteration of phospholipid composition and role of inflammation. (15th June 2017) - Giraud, C; Capel, F; Dutheil, F; Pereira, B; Soubrier, M; Kontush, A; Lhomme, M; Sebedio, JL; Tournadre, A
Abstract : Background: Rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylsosing spondylitis (SA) are associated with an increased cardiovascular (CV) mortality. Quantitative abnormalities in lipid profiles are insufficient to explain this excess of CV risk and a qualitative approach of HDL composition is required to identify loss of atheroprotective functions and to correctly identify patients at risk. Atheroprotective functions of HDL are directly linked to the structure of HDL mainly composed of phospholipids (PL). Objectives: The main objective of this study is to analyze the PL composition of HDL in patients with chronic inflammatory rheumatic diseases and to compare to matched healthy controls. Methods: HDL structure was assessed in patients with active RA (ACR criteria), PsA (CASPAR criteria) and SA (ASAS criteria) patients before initiating first biologic and in healthy controls matched for age, sex and body mass index. Dyslipidemia treatment or pathology which could interfere with lipid profile were excluded. Demographics data, disease activity, cardiometabolic profile and plasma samples were collected. HDL particle were isolated from plasma after two step ultracentrifugation using gradient of density. Lipidomics analysis were performed using liquid chromatography coupled with mass spectrometry. Phospholipid composition between patients and controls was compared using multivariate analyses to take into account possible confounding variables determined according to univariate results and clinical relevance (age, tobacco consumption, steroids use). Multidimensional analyses as factorial mixed data analysis (FMDA) were performed to complete these analyses. Results: 19 RA, 19 PsA and 12 SA were analyzed (table 1 ). 220 phospholipids species were identified among which 2 major classes were modified in rheumatic diseases. Phosphatidylcholine (PC) decreased in RA and PsA (p<0.01 and <0.05 respectively) while lysophosphatidylcholine (LPC) increased significantly (p<0.01, and <0.05 respectively). Some phospholipids species as PC 40: 8 (p<0.001), LPC 16:0 (p<0.001), LPC 18:0 (p<0.001) were identified as discriminant marker of HDL composition in rheumatic disease as compared to controls. Conclusions: Phospholipids composition of HDL is altered in RA and PsA. These alterations could explain a loss of atheroprotective functions and the excess of CV risk observed in RA and PsA patients. Chronic inflammation, through the activation of phospholipase A2 type II which hydrolyze PC into LPC, could modify the structure of HDL phospholipids and thus could impact HDL functionality such as cholesterol efflux, LDL oxidation modulation, anti-inflammatory and vasculoprotective properties. These preliminary data suggest the major role of inflammation in these alterations. References: Tselepis AD et al. Atheroscler Suppl. 2002;3(4):57–68. Kontush A, et al. J Lipid Res. 2013;54(11):2950–63. Disclosure of Interest: None declared